Need to improve clinical trials in rare neurodegenerative disorders - Maria Puopolo; Maurizio Pocchiari (Istituto Superiore di Sanità, 2011)
Rare neurodegenerative diseases are fatal and no therapy is available to cure or slow down the progression of disease. We report possibly weaknesses in the management of clinical studies in these diseases, ranging from poor preclinical studies, difficulties in the recruitment of patients, delay in the onset of treatment because of lack in early disease-specific biomarkers, and suboptimal design of Phase II clinical trials. The adoption of innovative statistical approaches in early Phase II trials might improve the screening of drugs in rare neurodegenerative disorders, but this implicates efforts from clinical researchers, statisticians, and regulatory people to the development of new strategies that should maintain rigorous scientific integrity together with a more ethical approach to human experimentations.